Understanding of Moderation Verses in Books Published in 2014 and 2017 Perspective of Jurgen Habermas' Ideology Criticism - Abdul Ghofur; Abdul Najib; Ahmad Musonnif Alfi (AL-ISHLAH: Jurnal Pendidikan, 2023)
Pendidikan Agama Islam dan Budi Pekerti (PAIBP), published by Kementerian Pendidikan dan Kebudayaan in 2014 and 2017 book was the main source for high schools in Indonesia. But, a previous study found that this book contained some radicalism value meanwhile, the government tried so hard to eradicate it through a moderation campaign. However, this book still contains some themes of moderation in the discussions such as unity (ukhuwah), tolerance and democracy which would be the focused of this study. This research then aims to review some article of the Qur`an that contains moderation value to gain explanation, discussion and easy implementation. The framework of this study was ideology critics by Jurgen Habermas which consisted of two steps of research to find technical understanding and reflected understanding. The technical understanding was found by several field investigations using observation in all 9 public senior high schools in Rembang regency and interviews with the PAI teacher and also the students from all levels with snowballing sampling. This study found that technical understanding of this book stopped at normative-definitive comprehensions while the implementations could not be done because this book's explanations were too short. It was also influenced by the understanding of the teachers and the teaching style of the teachers that was very subjective. The only implantation founded was reading the qur’an verses by ilm tajwid. The reflective understanding was found by a series explorations of Qur’anic exegesis books and several Islamic classical literature. The results of this study shows that this book could be upgraded by (1) extended the meaning of ukhuwah (2) limitations of the practice of tolerance and (3) additions discourse of democracy in the field of sharia and contextualization of democracy in the context of Indonesia.